KEANEKARAGAMAN JENIS BURUNG DI HUTAN PRIMER DI SUAKA MARGASATWA PULAU PASOSO KECAMATAN BALAESANG TANJUNG KABUPATEN DONGGALA - Karar, Abd.; Ningsih, Sri; Ihsan, Moh. (Jurnal Warta Rimba, 2016)
Pasoso Island is one of the islands located in the Makassar Strait. Although this area was made a conservation area because of the presence of the two sea turtles species, but other animals’ life on the Pasoso Island are also important, such as avivauna (birds) which can be found in significant amounts. Birds are wild animals that live in nature and have an important role in preserving the environment, such as pest control, seed dispersers and pollinators. The suitable environment that is considered as a habitat for birds would provide food, shelter and breeding grounds for birds. This study was conducted from September to November 2014 with the composition of bird species, the presence, diversity, evenness and the presence in the area of ​​primary forest in Pasoso Island Balesang Tanjung sub district of Donggala district. Method used for data collecting on the area of ​​primary forest in the region of Pasoso Island Wildlife was transect method, and the length was 500m transect. The composition of the observations in the morning and in the afternoon encountered 14 types of birds, including 12 in the family. Furthermore, there were 2 types of Sulawesi endemic birds from 14. Based on the attendance at observation level, there was 1 bird species which has the presence of 60%, 1 type got 50%, 1 type got 40%, 2 types got 30%, and 8 types of 10%. The diversity index in the morning observation was H 1.8728 and 1.7301 H was in the afternoon. Evenness index in the morning observation E was 1.872821 while the afternoon E got 1.730074. The observation in the morning was 64 compositions while in the afternoon; there was a sighting of 93 species of birds’ composition. Keywords: Diversity, Bird, Primary Forest, Pasoso Island